PERLINDUNGAN HUKUM TERHADAP HAK KONSUMEN TERKAIT PENYALAHGUNAAN ALAT KESEHATAN RAPID TEST ANTIGEN BEKAS BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Oldriana Lavenia Kumurur; Christine S.T. Kansil (Jurnal Hukum Adigama, 2021)
The Indonesian government has an obligation to protect every citizen in any situation and condition. Protection from the government must be given to the community if there is an impact, not only to the community but also to an impact that occurs in the economy and politics on the government. Since March 2020 until now, Indonesia is facing a coronavirus pandemic. Due to the virus, the government issued Government Regulation Number 21 of 2020 concerning Government Regulation (PP) concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of CoronaVirus Disease 2019 (COVID-19). One of the policies is the rapid antigen test to prevent the spread of the virus and as a condition for traveling outside the city. In addition to being regulated by the Minister of Health, consumers are given protection according to Law Number 8 of 1999 concerning Consumer Protection. Consumers are given rights that are guaranteed and protected by the government in Article 4 of the consumer protection law. Despite having two regulations, it turns out that in the field there are still cases of misuse of medical devices by the perpetrators. One of the business actors who abused the rapid test medical device at Kualanamu Airport, North Sumatra. The formulation of the problem in this study is how the legal protection of consumer rights related to the misuse of used antigen rapid test medical devices is based on Law Number 8 of 1999 concerning Consumer Protection. The method used; normative juridical, with the types and sources of secondary, primary, tertiary data. The results of the research are that consumer protection in medical devices for rapid tests is still lacking in supervision and guidance, resulting in violations of the law in the health sector and harming many consumers.